Perjuangan Masa Sekolah Sebagai Inspirasi Penciptaan Karya Seni Lukis - Angling Yoga Bayu; Satriana Didiek Isnanta (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
The creation of this final project entitled The Struggle for the School Period as an Inspiration for the Creation of Painting Art is a response to the author's experience of being part of rural children who have dreams of studying in a big city. The limit of the discussion is on the struggle of a child in an underprivileged family, determined to study at the SMK level in Solo, which tends to require a lot of money than school in the village. The struggle for the school period is a form of effort to complete the study period smoothly even though there are constraints. The purpose of the creation of this final project is to create a work of art that painting inspiration from the struggles of the school period by explaining the concept of its creation, the process of its creation and the meaning of the artwork created. The creation of works refers to the three stages of creation proposed by Herman Von Helmholtz, including the stages of collecting facts, data and sansation, the deposition stage and the stage of expressing the form of an artwork. This final project produces six works of decorative-surrealistic painting that emphasize visual forms by cultivating stylization, deformation and transformation using acrylic paint on canvas media and using plaque and sungging techniques as ideas for color processing.Keywords: school period struggle, painting, decorative-surrealistic, sungging